APPLICATION OF TARIFF PREFERENCES IN DEVELOPED COUNTRIES THAT ARE MEMBERS OF THE WORLD TRADE ORGANIZATION - Soatov Sanjar Sarvarovich (Scholar Express Journals, 2023)
This article is devoted to revealing the importance of tariff preferences applied in accordance with the customs legislation of the two developed countries, the United States, Japan and the European Union, which are members of the World Trade Organization.
Keywords: World Trade Organization; United Nations Conference on Trade and Development; tariff preferences